Numerical analysis of un-steady heat distribution in heatsink using finite different method - Fahendri Fahendri (PILLAR OF PHYSICS, 2014)
Heatsink is one of the multiple device of coolant on computer or electronics device commonly made of metal. Heatsink as cooler is very interesting to be analyzed the model of its heating distribution. The purpose of the research is to analyse the model of transient heating distribution and the influence of material heatsink at the model of heat distribution which is produced. The methods which is used on the research is finite different that functions to get model of heating distribution. It is a the descriptive research namely modeling heat distribution at heatsing and comparing it with existing theory. The result of research indicates that heat distribution model at heatsink is almost  spread evenly. The material  of heatsink has an influence towards heat distribution of heatsink. The large value material of conductivity has a better heat distribution